2014
DOI: 10.1038/ejhg.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated copy of CHRNA7 increases risk and worsens prognosis of COPD and lung cancer

Abstract: Recent genome-wide association studies implicated that the nicotinic acetylcholine receptors (nAChRs) are common susceptible genes of two contextual diseases: chronic obstructive pulmonary disease (COPD) and lung cancer. We aimed to test whether the copy number variations (CNVs) in nAChRs have hereditary contributions to development of the two diseases. In two, two-stage, case-control studies of southern and eastern Chinese, a common CNV-3956 that duplicates the cholinergic receptor, nicotinic, α7 (CHRNA7) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…As described in previously published studies52829, a two-stage case-control study was conducted in the southern Chinese and eastern Chinese population. In brief, 1025 COPD patients and 1061 controls were enrolled from Guangzhou city; 486 COPD patients and 616 controls were recruited from Suzhou city.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in previously published studies52829, a two-stage case-control study was conducted in the southern Chinese and eastern Chinese population. In brief, 1025 COPD patients and 1061 controls were enrolled from Guangzhou city; 486 COPD patients and 616 controls were recruited from Suzhou city.…”
Section: Methodsmentioning
confidence: 99%
“…However, these loci by no means cover the complete genetic predisposition of COPD, because they mainly focus on single nucleotide polymorphism (SNP). Copy number variation (CNV)45 also contributes to COPD heritability67. CNVs can hold greater influence over covering genes than SNPs do, because CNVs can cause changes in a large DNA fragment while SNPs can only cause one base change8.…”
mentioning
confidence: 99%
“…Because of its high calcium permeability which modulates intracellular signaling molecules (11), the homopentameric α7 type of nAChRs (α7-nAChR) has been implicated in lung tumorigenesis (1214). A recent study has showed that the copy number variations (CNV-3956) which resulted in a duplicated α7-nAChR conferred to an increased risk of lung cancer and poor survival of lung cancer patients (15). Treatment with NNK, which binds with high affinity to α7-nAChR, increases the expression of α7-nAChR in papillomavirus-immortalized bronchial epithelial cells (13), as well as cell proliferation and cell motility (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of lung cancer depends on the copy number of the CNV at 16q23 containing oxidoreductase (WWOX); the deletion genotype of the CNV increases the risk of lung cancer (OR = 1.39). Recently, Yang et al have reported that ≥4-copy of CNV in the nicotinic acetylcholine receptors (nAChRs) increase risk of lung cancer [59]. Lung cancers are classified into histological subtypes for the difference in therapeutic regimen.…”
Section: Lung Cancermentioning
confidence: 99%